2018
DOI: 10.1111/corg.12233
|View full text |Cite
|
Sign up to set email alerts
|

Do talented managers invest more efficiently? The moderating role of corporate governance mechanisms

Abstract: Manuscript type Empirical Research question/issue The main objective of this paper is to examine the influence of managerial ability on investment efficiency. Using a sample of 2185 firms from 24 countries for the period 2006–2015, we hypothesize a positive association between investment efficiency and managerial ability and suggest that able managers make fewer over‐ and underinvestment decisions. As a unique and helpful feature of this study, we also employ a model to capture the different interactions betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
26
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 83 publications
5
26
1
2
Order By: Relevance
“…We show that firms with higher (lower) managerial ability exhibit smaller (greater) deviations from predicted investments as tax avoidance increases. In this respect, we extend the work of Garcia‐Sanchez and Garcia‐Meca (), who show, using cross‐country data, that managerial ability is an important determinant of investment efficiency. Our contribution stems from focusing on funds generated through tax avoidance activities and showing that the relation between corporate tax avoidance and investment efficiency is conditional on managerial ability.…”
supporting
confidence: 66%
See 2 more Smart Citations
“…We show that firms with higher (lower) managerial ability exhibit smaller (greater) deviations from predicted investments as tax avoidance increases. In this respect, we extend the work of Garcia‐Sanchez and Garcia‐Meca (), who show, using cross‐country data, that managerial ability is an important determinant of investment efficiency. Our contribution stems from focusing on funds generated through tax avoidance activities and showing that the relation between corporate tax avoidance and investment efficiency is conditional on managerial ability.…”
supporting
confidence: 66%
“…() argues that more able managers can better gauge the timing and magnitude of economic returns from investments, as well as better assess the risks and returns associated with investments. Consistent with this argument, Garcia‐Sanchez and Garcia‐Meca () find that managerial ability is an important determinant of investment efficiency, resulting in lower levels of under‐ or over‐investment. To the extent that funds generated through tax avoidance activities are an important source of capital, especially for financially constrained firms (Edwards et al ., ), we expect that compared to managers with lower ability, managers with higher ability use the proceeds from increased levels of tax avoidance to improve investment efficiency.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, Agrawal and Cooper [19] oppositely showed that bad governance mechanisms would follow accounting scandals. Garcia-Sanchez and Garcia-Meca [20] further argued that governance mechanisms are effective to cover inefficient investment decisions. At the last, Horstmeyer [21] studied internal monitoring as the internal governance concerns.…”
Section: Corporate Governancementioning
confidence: 99%
“…Introduction of the managerial ability measure by Demerjian et al (2012) spawned a new literature examining how managerial ability affects various aspects of managers' decision-making. These studies have documented that managerial ability has a distinctive effect on a firm's financial reporting quality and earnings quality (Demerjian et al, 2013;Huang & Sun, 2017;Wang, Chen, Chin, & Zheng, 2017), earnings management activities (Skousen, Sun, & Wu, 2019), accounting and disclosure policies (Abernathy et al, 2018;Baik et al, 2011;Luo & Zhou, 2017;Sun, 2016), information environment (Baik et al, 2018), tax avoidance behaviour (Koester, Shevlin, & Wangerin, 2017), investment practices (Andreou et al, 2017;Gan, 2019;García-Sánchez & García-Meca, 2018;Habib & Hasan, 2017;Lee et al, 2018), risk-taking behaviour (Andreou et al, 2016;Yung & Chen, 2018), innovation activities (Y. Chen, Podolski, & Veeraraghavan, 2015), credit ratings (Bonsall, Holzman, & Miller, 2017;Cornaggia, Krishnan, & Wang, 2017), structure and pricing of debt (Bui, Chen, Hasan, & Lin, 2018;De Franco, Hope, & Lu, 2017;Petkevich & Prevost, 2018), dividend policies (Guan, Li, & Ma, 2018;Jiraporn, Leelalai, & Tong, 2016); audit fees (Gul, Khedmati, Lim, & Navissi, 2018;Li & Luo, 2017); firm performance (Banker, Darrough, Huang, & Plehn-Dujowich, 2013;Cox, 2017;Demerjian et al, 2012;Francis, Hasan, Mani, & Ye, 2016), and corporate social responsibility (CSR) performance …”
Section: Managerial Ability and Investmentmentioning
confidence: 99%